A synthesis of radial growth patterns preceding tree mortality. (12th November 2016) - Cailleret, Maxime; Jansen, Steven; Robert, Elisabeth M. R.; Desoto, Lucía; Aakala, Tuomas; Antos, Joseph A.; Beikircher, Barbara; Bigler, Christof; Bugmann, Harald; Caccianiga, Marco; Čada, Vojtěch; Camarero, Jesus J.; et al.
Abstract: Tree mortality is a key factor influencing forest functions and dynamics, but our understanding of the mechanisms leading to mortality and the associated changes in tree growth rates are still limited. We compiled a new pan‐continental tree‐ring width database from sites where both dead and living trees were sampled (2970 dead and 4224 living trees from 190 sites, including 36 species), and compared early and recent growth rates between trees that died and those that survived a given mortality event. We observed a decrease in radial growth before death in ca. 84% of the mortality events. The extent and duration of these reductions were highly variable (1–100 years in 96% of events) due to the complex interactions among study species and the source(s) of mortality. Strong and long‐lasting declines were found for gymnosperms, shade‐ and drought‐tolerant species, and trees that died from competition. Angiosperms and trees that died due to biotic attacks (especially bark‐beetles) typically showed relatively small and short‐term growth reductions. Our analysis did not highlight any universal trade‐off between early growth and tree longevity within a species, although this result may also reflect high variability in sampling design among sites. The intersite and interspecific variability in growth patterns before mortality provides valuable information on the nature of the mortality process, which is consistent with our understanding of the physiological mechanisms leading to mortality. Abrupt changes in growth immediately before death can be associated with generalized hydraulic failure and/or bark‐beetle attack, while long‐term decrease in growth may be associated with a gradual decline in hydraulic performance coupled with depletion in carbon reserves. Our results imply that growth‐based mortality algorithms may be a powerful tool for predicting gymnosperm mortality induced by chronic stress, but not necessarily so for angiosperms and in case of intense drought or bark‐beetle outbreaks.